A genre-based study of Chinese argumentative essays written for secondary school students in Malaysia - Chung, Vui Lin (2019)
The writing of argumentative essays constitutes an important component of the Chinese language as a single subject in secondary schools in Malaysia. Nonetheless, teachers often notice that students avoid writing argumentative essays owing to their lack of confidence in planning and writing this type of essays. Students do not have sufficient knowledge about the language resources needed to present different parts of an argumentative essay even though it is a major academic genre at upper secondary school level. This may be ascribed to the possibility that students are generally unaware of how to write an acceptable and presentable argumentative essay using appropriate strategies and language expressions. In this regard, the present study aims to (i) identify the range of communicative functions as reflected in the rhetorical moves and steps in Chinese argumentative essays, and (ii) explore how these steps are realised using various lexico-grammatical resources. With respect to methodology, this study (i) employed a basic move-step analytical framework proposed by Swales (1990, 2004), (ii) selected information elements (resembling claims and reasons) suggested by Toulmin (1958), (iii) a modified generic structure initiated by Hyland (1990) for argumentative essays, and (iv) a sequence for analysing linguistic mechanisms in relation to rhetorical steps as demonstrated by Wong and Lim (2014) for short essays. Identification and descriptions of salient language resources in the essays were largely based on the categories of linguistic expressions explained by Yip and Rimmington (2004) and Ross and Ma (2006). Three specialist informants were also invited to provide additional information on the percentages of texts containing specific text segments, the use of prominent language resources, and some practices in the context of writing argumentative essays at upper secondary school level. Based on the analysis, the researcher has found that professional writers of argumentative essays employ a total of four major moves, comprising ‘introducing a topic’, ‘making a claim’, ‘contending with a counter-argument’ and ‘drawing a conclusion’, each of which comprises two rhetorical steps. Although an argumentative essay may contain eight rhetorical steps, it has been observed that only ‘raising a claim’ and ‘justifying the claim’ are obligatory rhetorical steps. While ‘presenting a hook’, ‘reaffirming the claim’ and ‘broadening the context of the proposition/claim’ constitute rhetorical steps that occur in the majority of the argumentative essays, writers rarely contend with their perceived opponents using counter-arguments, thus explaining why ‘signaling a counter-argument’ and ‘rejecting a counter-argument’ constitute only optional steps that appear in a minority of the essays. What appear more interesting are a broad array of recurrent language resources, some of which appear in only a specific rhetorical step although it has been found that similar lexico-grammatical structures may occur in several rhetorical steps in accordance with the writers’ strategies. Based on the findings, related recommendations are made in regard to how Chinese language instructors can flexibly use the move-step framework identified in this study to help novice writers learn to write argumentative essays by associating specific language resources with communicative functions in the rhetorical steps concerned. The results of this study are also of significance to academicians who are interested in devising courses that include a component about the writing of argumentative essays in secondary schools or tertiary institutions where Chinese is learnt as an additional language.